Identity Maintainment And Communicational Barrier For Immigrant Tribe (A Study Case of Kampung Bogor Village in Kepahyang District, Bengkulu) - Alfarabi Alfarabi; Adiella Yangkie Lubis (Communication Sphere, 2015)
ABSTRACTHow the identity is maintained by immigrant tribe within a local tribe territorial is the mainfocus of this research. Cultural background differences in maintaining identity is one of thecausal factor in communicational barrier between immigrant tribe and local tribe at KampungBogor village in KepahyangDistric, Bengkulu. Different perspective arises because of culturalbackground differences is causing suspicion and jealousy in which hasn‟t appear yet but stillmaking it as a cause for latent conflict to arise in the form of perception and how they think. Thisresearch is using qualitative descriptive approach with participatory observation method, indepth interview, and focus group discussion to collect the research data. Qualitative approachwill make the data of this research to be deeply recover without affecting the natural conditionon the field. The result of this research states that latent conflict that arise between two tribes isconnected to the tribe identity built by Bogor tribal residence. This identity gives a positive labelto the ingroup as to have consequence, a negative label to the outgroup. The main factor forcommunicational barrier between tribes are language and bogornese perspective on how theyplace their own kind to fulfill basic needs in life. As for the factor that makes communication dohappen between two tribes is bogornese kind and polite attitude that choose to avoid conflictwith other tribes by succumb to it. This kind and politeness label tend to make outsiders to buildrelation with the bogornese and doing so with certain boundaries. Recommendation that isgiven in this research suggest that either equality views in tribe differential and not negativelabeling other tribes are both needed.Keywords: Identity, Latent Conflict, Communicational Barrier, Tribe